America's changing icons : constructing patriotic women from World War I to the present - Babic, Annessa Ann (Fairleigh Dickinson University Press, 2018)
America's Changing Icons examines nationalism and gendered national roles via the lens of popular culture, to explore the discursive and at times chaotic ways American society interprets itself. This multi layered examination delves into the iconography and role of American women, and their evolution, from World War I to the present.